(untitled) (New York, NY, 2002)
The definitive cell biology textbook thoroughly revised to provide readers with a cutting-edge account of modern biology. New material on genomics, protein structure, stem cell and genetic diseases.
Keywords: Cytology,Molecular biology,Sinh học phân tử,Tế bào học